Evaluation of physicians and junior residents’ knowledge and awareness of radiation dose and its risks: a cross-sectional survey in tertiary health centre of central India - Gour, Sushil; Kumar Maurya, Rajesh; Pratap Singh, Punya; Sharma, Himanshu; Maravi, Prashant (International Journal of Research in Medical Sciences, 2017)
Background: The frequency of radiological investigations increases to many fold now-a-days, so it is necessary to know the knowledge of all physicians about radiation dose, safety measures and regulations which governs the use and practice of radiation examination and their therapeutic use. The objectives comprise to investigate amongst all Physicians: (1) level of knowledge and awareness of radiation dose of radiological investigations and radiobiology of radiation exposure, and (2) to assess physicians’ knowledge about the risks associated with the use of radiological examinations and their safety measures. Methods: A questionnaire targeting about knowledge, safety measures, and radiation biology about some commonly performed radiological procedures was addressed: (1) Relative radiation doses, (2) Associated risks of radiation exposure, (3) What safety measures should be considered before examination. (4) What risk and hazards all physicians considered when requesting radiological examinations. Results: A questionnaire answered by physicians demonstrates loops in knowledge. In all, 15% (14/92) incorrectly believed that magnetic resonance imaging involved radiation exposure and 3% (3/92) incorrectly believed that ultrasound involved radiation exposure; 38% (35/92) stated that they always explain the benefits and risk of radiation to their patients when obtaining informed consent for examinations involving radiation. Conclusions: This study concluded a deficit of knowledge about radiation dose exposure, and hazards among Physicians, which may cause them to request more radiological investigations than appropriate and high-dose investigations instead of lower dose alternatives. Providing better radiation protection training may help improve their basic knowledge on the subject and reduce unnecessary patient exposure to radiation.